Perspective trends in the design of Multifunctional Residential Units (MRUs) in the Russian Arctic: A discussion of potentials and challenges to their implementation - Dunichkin, Ilya V.; Bleil de Souza, Clarice; Bogachev, Konstantin V.; Korobeynikova, Anna E.; Shchekaturova, Natalia R. (2019)
Intensive development is carried out in the Arctic zone of the Russian Federation (AZRF) with complex modernization of transport networks and infrastructure of various types through the design, construction of Multifunctional Residential Unit (MRU) and the reconstruction of existing terminals and stations. The problem of developing new and reconstructing existing infrastructure in the Arctic has not only socio-economic, technological and planning components but fundamentally any development needs to account for extreme climatic conditions which affect urban conception and operation. This paper focuses on discussing important features of MRU developments. It shows examples of two case studies of MRU settlements considering the challenges involved in their design, further expanding the discussion in relation to the inclusion of green spaces in these settlements as well as in relation to safety and protection of pedestrians, moving between different buildings in ‘enclosed’ roads.